Fatigue Life Prediction For Small Component Welds - Yusman, Muhammad Syafiq Farhan (Universiti Sains Malaysia, 2022)
Almost all mechanical structures that adopts weld joints as connection method is susceptible to fatigue failure when operating load is applied repeatedly. In semi-automatic honeycomb cookies dipping machine, the weld components connecting rose-shaped mould to the moulding frame becomes the most critical location in the structure since the mould tend to be detached from the frame after long operational time resulting in reduction of manufacturing quantity. The suspected causes of this problem are due to vibration fatigue and thermal fatigue. Vibration fatigue is resulting from repetitive shaking process whereas thermal fatigue resulting from repetitive thermal changes during dipping and frying process. By applying finite element method (FEM) using ANSYS Mechanical software, simulations for both scenarios have been conducted to study the fatigue behavior of weld components on moulding frame structure. At the end of this study, the results show that the thermal fatigue is the main factor to the failure that occurs on the weld components. The maximum stress that occurs on the moulding frame structure due to vibration is 12.6 MPa. The stress magnitude is too low to induce fatigue damage since it far below the fatigue endurance limit of materials applied. The results for thermal fatigue analysis show that the moulding frame with 4 weld joints is the most critical in the whole moulding frame structure. The minimum fatigue life for this model is 21 cycles of dipping and frying process. Furthermore, the graphical approach of fatigue life prediction at any stress value has been achieved by plotting the stress-life (S-N) results for all moulding frame models. An experimental study will be required to support the reliability of the results obtained from the simulation since a few parameters that naturally occur on experimental approach such as welding flaws cannot be included in simulation.